Aliquanto post suspexit ad caelum et inquit: The Aratea and Prognostica across Cicero’s works - Raschieri, Amedeo Alessandro (Ciceroniana On Line, 2019)
Throughout his life, Cicero paid considerable attention to astronomical and meteorological issues, and specifically he focused on the work of Aratus. For this reason, it is not possible to isolate the Aratea (Phaenomena and Prognostica) in Cicero’s younger years or to study their presence in his other works merely to extract textual fragments or to derive historical information about their composition. The purpose of this study is to follow the cosmological and meteorological theme through the various literary genres and to reveal its connection to other aspects of Cicero’s work. In particular, this research addresses Aratus’ citations in the Epistulae ad Atticum, De re publica, De legibus, Orator, De natura deorum and De divinatione. Cicerone prestò molta attenzione alle questioni astronomiche e meteorologiche e, in particolare, per tutta la sua vita, alle opere di Arato. Per questo motivo, non è possibile isolare gli Aratea (i Phaenomena e i Prognostica) negli anni giovanili di Cicerone o studiare la loro presenza nelle altre sue opere solo per estrarre frammenti testuali o per ricavare informazioni storiche sulla loro composizione. Lo scopo di questo studio è seguire il tema cosmologico e meteorologico attraverso i vari generi letterari e trovare le connessioni con altri interessi e aspetti del lavoro di Cicerone. In particolare, la ricerca riguarda le citazioni di Arato in Epistulae ad Atticum, De re publica, De legibus, Orator, De natura deorum e De divinatione.